The termite genus Glyptotermes (Isoptera: Kalotermitidae) in Miocene amber from Ethiopia. (March 2022) - Bouju, Valentine; Jouault, Corentin; Perrichot, Vincent
Abstract: A new species of drywood termite (Isoptera: Kalotermitidae) is described from a nearly complete alate specimen preserved in early Miocene Ethiopian amber. Glyptotermes abyssinicus new species is distinguished by its U-shaped head with 12-segmented antennae, the ocelli separated from the eye margin, the right mandible with an obtuse angle between the apical and first marginal teeth, the left mandible with an obtuse angle between the apical and first + second marginal teeth, and the wing venation. This is the first termite reported from Ethiopian amber, and the fourth Miocene species of the extant genus Glyptotermes Froggatt, 1897, together with species previously described from diatomites of China and amber from the Dominican Republic. As the oldest report of the genus known from Africa, G . abyssinicus n. sp. constitutes an interesting new record for the biogeographical history of the kalotermitid lineage. UUID: http://zoobank.org/7670b045-fb31-4809-8116-4d14c4dd275b